Kinetic separation of hexane isomers by fixed-bed adsorption with a microporous metal-organic framework - Patrick S. Bárcia (2007)
A three-dimensional microporous metal-organic framework Zn(BDC)(Dabco)(0.5) (BDC = 1,4-benzenedicarboxylate, Dabco = 1,4-diazabicyclo [2,2,2]octane), having two types of intersecting pores to encapsulate linear hexane and to block branched hexanes, and thus exhibiting highly selective sorption with respect to n-hexane, has been successfully applied to the kinetic separation of hexane isomers by fixed-bed adsorption.